ANALYSIS OF BORDERS OF APPLICABILITY OF DEFINITION BY GENUS AND DIFFERENTIA - Дуцяк, І. З. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Empiric research of definitions which are contained in explanatory dictionaries and scientific editions is executed. It is set that definition by genus and differentia is not universal. Investigated The construction of definitions based on other principles are investigated.